Barriers for practicing BIM in facilities management in Indonesia [electronic resource] - Mehmood Ali Choudhary, 1971-; Maizan Baba, supervisor; Fakulti Geoinformasi dan Harta Tanah (2014)
Thesis (Sarjana Pengurusan Aset dan Fasiliti) - Universiti Teknologi Malaysia, 2014